Clean synthesis of novel green surfactants - Baheti, Payal Arvindkumar (2019)
Star polymers have attracted considerable attention because of their unique thermal and mechanical properties. At the same time, as sustainable chemistry is growing in impact at an unprecedented rate, we propose in this work to implement a greener pathway for the synthesis of star D-sorbitol-poly(ε-caprolactone) (star PCL-OHx) using clean solvents (polymerisation in the bulk or in supercritical CO2) and either FDA-approved Sn(Oct)2 catalyst or enzyme catalyst (Novozym® 435). The influence of these parameters on the star architecture (number of arms, MW of arms etc.) was rigorously analysed and corroborated with various analytical techniques (1H NMR, SEC-MALS, SEC-UC, phosphitylation quantitative 31P NMR approach). Linear monohydroxy PCL-OH and dihydroxy telechelic HO-PCL-OH samples were also prepared. The PCL materials obtained were used as hydrophobic macroinitiators for the polymerisation of cyclic hydrophilic ethylene ethyl phosphonate monomer for the synthesis of a range of different amphiphilic materials (i.e. star diblock, linear diblock and triblock copolymers). Self-assembly behaviour in aqueous solution of these copolymers was investigated by DLS, TEM and cryo-TEM. Triblock and star amphiphilic copolymers were revealed to be able to reduce the surface tension (γ) of water down to 45 mN m-1. Finally, enzyme catalysed star PCL-OHx polymers were functionalised with carboxylic end-groups using maleic anhydride. Water-dispersible surface-active ionic star polymers were then obtained. These maleate-functionalised star polymers were then photopolymerised with a small amount of tri(ethylene glycol) divinyl ether (~9wt% of total composition). The UV-cured crosslinked star PCL films produced were then analysed by FTIR, DSC and TGA.